"A Traitor to His Class": Race and Publisher W.E. "Ned" Chilton III, 1953–1984. Issue 2 (1st July 2016) - Simpson, Edgar
Abstract : This study looks historically at the role of the press in the public sphere, using as a case study the evolution of the views of publisher W.E. "Ned" Chilton III on race issues during his career at The Charleston Gazette, West Virginia's largest newspaper. The study commences during Chilton's early years at the Gazette just before the Brown v. Board of Education decision and ends a few years before his death in 1987. Chilton, born into privilege, began his career in the family newspaper business as an unquestioning member of the white power structure. However, over time he became extremely vocal in pointing out injustices toward African Americans during the civil rights movement, often using The Gazette's editorial pages and reporting resources to do so. In examining Chilton's publishing career through textual analysis, interviews, his personal papers, and published reports of the time, one can see how a single newspaper publisher became the most vocal and possibly the most effective voice for change in West Virginia during the civil rights movement, thus illustrating the dynamic role of even a single press outlet in providing access to information for debate in the public sphere.